Navigating the Complexities of Diabetes Insipidus Worsened by Primary Polydipsia: A Case Report - Davoudi, Zahra; Haghighimorad, Maryam; Ghaemi, Farahnaz; Amirdosara, Mahdi; Ranjbar, Arezoo (Novelty in Biomedicine, 2026)
Background: Fluid-electrolyte balance is regulated within a narrow range in diabetes insipidus (DI). Coexisting Primary Polydipsia and the related phenomenon of hyponatremia cause considerable mortality and morbidity. Cases Report: A 70-year-old woman with a history of central diabetes insipidus was referred to our center with a provisional diagnosis of acute-onset hyponatremia due to increased usage of DDAVP spray, who was admitted and treated carefully. According to daily monitoring of electrolytes and urine output, switching from spray to nightly melt DDAVP administration, the patient continued to display symptoms of polyuria, polydipsia, and low sodium levels. It led to a psychiatric consultation due to suspicion of accompanying Primary Polydipsia after experiencing a stressful event. Prescription of anti-anxiety and sedative medications showed successful resolution of hyponatremia, highlighting the importance of personalized strategies in managing the multifactorial aspects of DI and PP. Conclusion: This case underscores the complexities and potential remedies for handling DI in patients with underlying psychiatric conditions, emphasizing the necessity of a collaborative approach to optimize patient outcomes.